2017
DOI: 10.1155/2017/5304391
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Squamous Cell Carcinoma Antigen, Cytokeratin 19 Fragment, and Carcinoembryonic Antigen Levels in Diabetic Nephropathy

Abstract: Objective We aimed to explore whether squamous cell carcinoma antigen (SCC), cytokeratin 19 fragment (Cyfra21-1), neuron-specific enolase (NSE), and carcinoembryonic antigen (CEA) are elevated in diabetic nephropathy (DN) and the association between urinary albumin-to-creatinine ratio (UACR) and tumor markers in diabetic patients. Methods Nondialysis patients with diabetes (n = 261) and 90 healthy controls were enrolled. DN was defined as an UACR ≥ 30 mg/g in the absence of a urinary tract infection or other r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…It is well known, that STM can be influenced by factors apart from malignancies, like infection, renal function impairment or trauma. 23–26 Thus, it seems likely, that CHT and associated complications like neutropenia, infections or tumor response to CHT itself may affect STM response and could explain the smaller effect on PFS in the CHT-ICI setting. Also, a majority of patients responded to CHT-ICI radiologically as well as concerning STM which leads to a clear imbalance in subgroups sample sizes that confines the validity of the reported results.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known, that STM can be influenced by factors apart from malignancies, like infection, renal function impairment or trauma. 23–26 Thus, it seems likely, that CHT and associated complications like neutropenia, infections or tumor response to CHT itself may affect STM response and could explain the smaller effect on PFS in the CHT-ICI setting. Also, a majority of patients responded to CHT-ICI radiologically as well as concerning STM which leads to a clear imbalance in subgroups sample sizes that confines the validity of the reported results.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review identified 30 papers reporting clinical factors potentially associated with the non-cancer specific elevation of serum SCC levels ( Figure S2 , Table 2 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Based on these data, the association between benign respiratory disease, benign skin disease, or renal dysfunction (RD, defined by an estimated glomerular filtration rate of <60 mL/min/1.73 m 2 over 3 months [ 46 ]) during the follow-up and the occurrence of SCC elevation was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Serum Cyfra21-1 is an effective diagnostic biomarker for cancers such as lung cancer and oral/oropharyngeal squamous cell carcinoma [10][11][12], and previous studies also confirmed that the diagnostic specificity and sensitivity of urinary Cyfra21-1 for bladder cancer were about 60-90% and 40-92%, respectively [8,[13][14][15][16]. Immunoassaybased techniques such as electro chemiluminescent immunoassay, enzyme-linked immunosorbent assay (ELISA) and immunochromatographic assay were most often used for urinary Cyfra21-1 detection [17][18][19]. These detection methods suffer from some problems.…”
Section: Introductionmentioning
confidence: 96%